Interaksi Sosial dan Toleransi di Kampung Juuk Manis di Karangasem Serta Manfaatnya Bagi Kehidupan Masyarakat Multikultur - Mahyuni, Ida Ayu Putu; Asmariati, Anak Agung Inten (Humanis; Vol 27 No 3 (2023)DO - 10.24843/JH.2023.v27.i03.p12, 2023)
Historically Juuk Manis Village was one of the 12 layers of settlements that surrounded Puri Karangasem as the center of government at that time. Social interaction and tolerance in Juuk Manis and its benefits for multicultural society are the focus of this study. From the results of research in the Karangasem village, especially in Juuk Manis, the population, apart from Balinese ethnicity who are Hindus, also have ethnic Sasak who are Muslims. The problem: First, how is the process of social interaction? Second, what are the forms of social interaction and tolerance and their benefits for the life of a multicultural society? One of the concepts currently being developed is the concept of multiculturalism. The multiculturalism approach is an alternative to preventing conflict in a society that is diverse in ethnicity, culture and religion. The point is the need for compromise and tolerance in diversity. The method used is the historical method, supported by the theory of hegemony. The results of this study show various forms of tolerance and are beneficial to the life of a multicultural society.